Assessment of awareness about epilepsy amongst students of the volgograd state medical university and estimation of epilepsy stigmatization - O. V. Belyaev; E. A. Zharkina; T. I. Konovalova (Русский журнал детской неврологии)
Background. Epilepsy remains one of the most stigmatized diseases; patients still experience multiple problems with education, employment, social functioning and family creation. Reducing the stigma will help to increase socialization of epileptic patients, hence, improving their quality of life.Objective: to assess the degree of awareness about epilepsy amongst junior and senior students of the Volgograd State Medical University (VolSMU) and to estimate the level of stigmatization of epilepsy. Materials and methods. For the purpose of the study, we developed a questionnaire containing 12 questions. A total of 508 students of medical and pediatric faculties of the VolSMU participated in the anonymous survey. Statistical data analysis was performed using Microsoft Excel. Conclusions. Despite the increasing awareness about epilepsy and first aid for this category of patients, senior students of the VolSMU still have erroneous social stereotypes about patients with epilepsy.